FAKTOR-FAKTOR YANG MEMPENGARUHI EMPLOYABILITY SKILLS PESERTA DIDIK DI SMK ENREKANG - Tanrasula; Mustari Lamada; Lahming (UNM Journal of Technology and Vocational, 2022)
This study aims to describe determine the effect of independent variables and dependent variables, namely competency skills (X1), extracurricular (X2), internship experience (X3) and Employability skills (Y). The research method is quantitative research with ex post facto research type. The population of this research is the students of class XII SMK TKJ Study Program in Enrekang with atotal of 198 students. Based on the results of the study, it can be concluded that: (1), the competency skills, extracurricular scouts and practical experience of vocational students in Enrekang are in the good category; (2) There is a significant and positive influence between competency skills, extracurricular and practical work experience on Employability skills.